Perfect phrases for perfect hiring : hundreds of ready-to-use phrases for interviewing and hiring the best employees - Davila, Lori (McGraw Hill professional., 2007)
Packed with hundreds of sample phrases and questions; this book arms you with the right words for every stage of the hiring process and gives you the communication help you need to get the best players on your winning team. --